American Journal of Agricultural Economics Volume 100: A Century of Publishing the Frontiers of the Profession. (3rd October 2018) - Lybbert, Travis J.; Beatty, Timothy K.M.; Hurley, Terrance M.; Richards, Timothy J.
Abstract: The American Journal of Agricultural Economics reached its 100 th volume this year. We take this landmark volume as an opportunity to reflect on the evolution of this leading field journal—and one of the original research journals in economics. We document changes in the editorial structure of the journal—from a sole editor‐in‐chief to the present system of four rotating co‐editors—and in the management of the publication process overseen by these editors. Using bibliometric analysis, we then track various trends in the journal over the past century. We assess changes in the structure of articles, including increased article length, reliance on mathematical modeling and empirical analysis, and the dramatic rise in collaborative publication in the form of expanding co‐author teams. We also explore changes in the degree of topical specialization and the geographic coverage of research published in AJAE . We use co‐authoring relationships to construct collaboration networks specific to the journal and document the striking increase in the density of these networks. We conclude with some perspectives on the implications of this century‐long evolution of the journal for the coming decades of pushing and publishing the frontiers of the profession.